Fiscal Decentralization and Economic Growth in Central and Eastern Europe - Andrés Rodríguez-Pose; Anne Krøijer (London School of Economics and Political Science (LSE), European Institute, 2010)
The majority of the literature on fiscal decentralization has tended to stress that the greater capacity of decentralized governments to tailor policies to local preferences and to be innovative in the provision of policies and public services, the greater the potential for economic efficiency and growth. There is, however, little empirical evidence to substantiate this claim. In this paper we examine, using a panel data approach with dynamic effects, the relationship between the level of fiscal decentralization and economic growth rates across 16 Central and Eastern European countries over the 1990-2004 period. Our findings suggest that, contrary to the majority view, there is a significant negative relationship between two out of three fiscal decentralization indicators included in the analysis and economic growth. However, the use of different time lags allows us to nuance this negative view and show that long term effects vary depending on the type of decentralization undertaken in each of the countries considered. While expenditure at and transfers to subnational tiers of government are negatively correlated with economic growth, taxes assigned at the subnational level evolve from having a significantly negative to a significantly positive correlation with the national growth rate. This supports the view that subnational governments with their own revenue source respond better to local demands and promote greater economic efficiency.
Keywords: 330; Fiscal decentralization; economic growth; efficiency; devolution; Central and Eastern Europe